2019
DOI: 10.1016/j.heliyon.2019.e01825
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil degradation in montane grasslands of North-eastern Italian Alps (Italy)

Abstract: Grasslands cover a large portion of the terrestrial ecosystems, and are vital for biodiversity conservation, environmental protection and livestock husbandry. However, grasslands are degraded due to unreasonable management worldwide, i.e., soil erosion indirectly due to the damage of overgrazing on vegetation coverage and soil texture. An in-depth investigation is necessary to quantify soil erosion in alpine pastures, in order to manage grasslands more sustainably. In this work, we collected freely available s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…The main consequence of under-grazing or complete disappearance of permanent pastures has been a progressive entry of shrubs and trees (Cislaghi et al, 2019), but also the abandonment of centuries-old land setting. As a consequence of rural exodus toward cities and coastal areas, in estimating soil degradation in mountain grasslands of the Autonomous Province of Trento (northeastern Italian Alps), Torresani et al (2019) observed that the increase in the number of livestock, combined with scarce grazing management and climatic and geomorphic processes, may lead to a general degradation of land setting systems in pastureland. In similar context, drastic interventions of sustainable management of grassland have to be planned in case of widespread erosion, so as to rehabilitate degraded lands, preventing soil losses, and introducing sustainable management of grassland.…”
Section: Venetomentioning
confidence: 99%
“…The main consequence of under-grazing or complete disappearance of permanent pastures has been a progressive entry of shrubs and trees (Cislaghi et al, 2019), but also the abandonment of centuries-old land setting. As a consequence of rural exodus toward cities and coastal areas, in estimating soil degradation in mountain grasslands of the Autonomous Province of Trento (northeastern Italian Alps), Torresani et al (2019) observed that the increase in the number of livestock, combined with scarce grazing management and climatic and geomorphic processes, may lead to a general degradation of land setting systems in pastureland. In similar context, drastic interventions of sustainable management of grassland have to be planned in case of widespread erosion, so as to rehabilitate degraded lands, preventing soil losses, and introducing sustainable management of grassland.…”
Section: Venetomentioning
confidence: 99%
“…In steep Alpine grasslands, shallow erosion is an abundant phenomenon, which results in a large number of relatively wellconstrained spots, where the bare earth (soil, unconsolidated sediments or bedrock) is exposed (Wiegand and Geitner, 2013). The development of such eroded areas can be initiated by different processes, such as trampling and grazing by cattle (Torresani et al, 2019), shallow landsliding (Cruden and Varnes, 1996), as well as abrasion and stripping of the vegetation and topsoil by snow gliding (Wiegand and Geitner, 2013;Höller et al, 2014).…”
Section: Erosion Studies Using Laser Scanningmentioning
confidence: 99%
“…In context to land restoration, degradation of high altitude pastureland leading to soil erosion nowadays have become a matter of great concern. Some of the examples of such lands include, montane grasslands of the north-eastern Italian Alps (Italy) 6 , Asteroussia Mountains (Greece) 7 , and High Himalayas in Nepal and India 8 .Therefore, restoration of alpine pastures is a global need. Some restoration guidelines available for low altitude forest and degraded lands include Restoration Opportunities Assessment Methodology (ROAM) 9 , International principles and standards for the practice of ecological restoration, Ecological Restoration Guidelines for British Columbia 10 and Assessing Landscape Restoration Opportunities for Uttarakhand, India, etc.…”
Section: Introductionmentioning
confidence: 99%